2023
DOI: 10.5498/wjp.v13.i4.149
|View full text |Cite
|
Sign up to set email alerts
|

Reducing psychiatric illness in the perinatal period: A review and commentary

Abstract: This brief overview highlights the global crisis of perinatal psychiatric illness (PPI). PPI is a major contributor to many adverse pregnancy, childbirth, and childhood development outcomes. It contributes to billions of dollars in spending worldwide each year and has a significant impact on the individual, their family, and their community. It is also highly preventable. Current recommendations for intervention and management of PPI are limited and vary considerably from country to country. Furthermore, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
0
0
0
Order By: Relevance
“…By the turn of the 21st century, the field of maternal mental health had grown beyond its myopic focus on child outcomes to encompass a wider classification of diagnoses (e.g., perinatal mood and anxiety disorders or PMADs), clinical windows (e.g., prenatal onset), pathophysiologies (e.g., traumatic childbirth), interventions (e.g., zuranolone), and trainings (e.g., specialized curricula)— this time to alleviate the distress of the mothers themselves ( 9 11 ). Epidemiological data revealed that vulnerability in motherhood was ubiquitous with estimates between 15% to 21% of the general population experiencing depression, and up to 80% of mothers reporting distress of some kind ( 12 ). This paradigmatic shift from viewing the mother merely as a functional object to recognizing her as a psychological subject marked a belated but critical turn.…”
Section: Introductionmentioning
confidence: 99%
“…By the turn of the 21st century, the field of maternal mental health had grown beyond its myopic focus on child outcomes to encompass a wider classification of diagnoses (e.g., perinatal mood and anxiety disorders or PMADs), clinical windows (e.g., prenatal onset), pathophysiologies (e.g., traumatic childbirth), interventions (e.g., zuranolone), and trainings (e.g., specialized curricula)— this time to alleviate the distress of the mothers themselves ( 9 11 ). Epidemiological data revealed that vulnerability in motherhood was ubiquitous with estimates between 15% to 21% of the general population experiencing depression, and up to 80% of mothers reporting distress of some kind ( 12 ). This paradigmatic shift from viewing the mother merely as a functional object to recognizing her as a psychological subject marked a belated but critical turn.…”
Section: Introductionmentioning
confidence: 99%